Tree Diversity in Home Gardens in the Bogor Regency, West Java - Dian A. Susanto; Kuswata Kartawinata; Nisyawati (The Ethnobiological Society of Indonesia, 2022)
We used the point-centered quarter method for trees and quadrats for saplings in home gardens of 42 hamlets within 40 districts in the Bogor Regency, West Java, to investigate the floristic composition and structure of home garden tree communities. We found a diverse range of fruit trees. A total of 64 fruit tree species were identified accounting for 93.2% of all tree species. Artocarpus heterophyllus and Nephelium lappaceum were the two species with the highest importance value, frequency, and degree of association. The Artocarpus heterophyllus–Nephelium lappaceum association or in the local names Nangka– Rambutan association is justified based on these species’ characteristics. The distributional patterns of tree species support categorizing them into six groups: very common, common, rather common, rather rare, rare, and very rare. Annona squamosa, Phyllanthus acidus, Syzygium polyanthum, Glochidion borneense, Mangifera foetida, and Diospyros philippensis were the fruit tree species that made up the extremely rare group. Nephelium lappaceum, Artocarpus heterophyllus, and Lansium domesticum, had the highest importance value (40%) at the tree level, whereas Punica granatum, Annona muricata, and Averrhoa bilimbi at the sapling stage. Species diversity indices for trees and saplings in the sampled home gardens fell into the H' = 1 to 3 categories, while similarity indices among the home gardens species composition were quite low (IS 64%). The fruit tree species had a low ability to regenerate.